Odpowiedź:
g) 3 • x + 2 = -19
3 • x = -19 - 2
3 • x = -21 /: 3
x = -7
Spr : 3 • (-7) + 2 = (-21) + 2 = -19
h) 6 • c - 10 = 14
6 • c = 14 + 10
6 • c = 24 /: 6
c = 4
Spr : 6 • 4 - 10 = 24 - 10 = 14
i) 8 • x + 3 = 43
8 • x = 43 - 3
8 • x = 40 /: 8
x = 5
Spr : 8 • 5 + 3 = 40 + 3 = 43
j) 5 • s - 9 = -6
5 • s = -6 + 9
5 • s = 3 /: 5
s = 0,6
Spr : 5 • 0,6 - 9 = 3 - 9 = - 6
k) 7 - 2 • x = 15
-2 • x = 15 - 7
-2 • x = 8 /: (-2)
x = -4
Spr : 7 - 2 • (-4) = 7 - (-8) = 15
l) 6 • k + 3 = 33
6 • k = 33 - 3
6 • k = 30 /: 6
k = 5
Spr : 6 • 5 + 3 = 30 + 3 = 33
Szczegółowe wyjaśnienie:
Pozdrawiam.